Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Literasi dan Berpikir Tingkat Tinggi Siswa - Sulistiyawati, Wardani; Kusmiyati, Kusmiyati; Tobing, Viktor Maruli L. Tua (Peneliti.net, 2024)
Teachers carry out innovations and new strategies in solving the social science learning problems above, namely by using the discovery learning learning model. Discovery learning learning provides opportunities for students to independently improve their literacy skills by reading, remembering, understanding, interpreting, and arriving at the ability to conclude information contained in reading, both individually and in groups. Familiarity with literacy activities in social science learning is expected to be able to improve students' high-level thinking abilities on a basic basis. The research objectives include: 1) The influence of the Discovery learning learning model on students' literacy skills in Class VI Social Sciences learning at UPTD SDN Ujung Piring Bangkalan, 2) The influence of the Discovery learning learning model on students' higher level thinking abilities in Class VI Social Sciences learning at UPTD SDN Ujung Piring Bangkalan, and 3) The influence of the Discovery learning learning model on students' high-level literacy and thinking skills in Class VI Social Sciences learning at UPTD SDN Ujung Piring Bangkalan. This research uses a quantitative approach and experimental research type. The research population and sample were 24 class VI students at UPTD SD Negeri Ujung Piring Bangkalan. The results of the research include: 1) There is an influence of the Discovery learning learning model on students' literacy skills in Class VI Social Sciences learning at UPTD SDN Ujung Piring Bangkalan, 2) There is an influence of the Discovery learning learning model on students' higher level thinking abilities in Class VI Social Sciences learning at UPTD SDN Ujung Piring Bangkalan , and 3) There is an influence of the Discovery learning learning model on students' higher level literacy and thinking skills in Class VI Social Sciences learning at UPTD SDN Ujung Piring Bangkalan.